Evaluation of Vision-Related Quality of Life after Autologous Internal Limiting–Membrane Transplantation for Refractory Macular Holes - Yuan, Dongqing (Clin Ophthalmol, 2020)
PURPOSE: To evaluate the vision-related quality of life of vitrectomy combined with autologous internal limiting membrane (ILM) transplantation for refractory macular holes (MHs). METHODS: There were 40 eyes with refractory MHs included, and all eyes received 23 G vitrectomy and ILM peeling with autologous ILM transplantation. Preoperative and postoperative basic conditions were recorded. The Chinese version of the vision-related quality-of-life scale was used to evaluate patients after operation. Quality of life, postoperative visual acuity, and size of MHs before operation were assessed with Spearman rank correlations. RESULTS: All patients were followed up for 3 months after surgery. Mean postoperative best-corrected visual acuity had significantly improved after surgery. Vision-related quality of life of patients after surgery was closely related to the MH index, but negatively correlated with best-corrected visual acuity before and after surgery. CONCLUSION: The anatomical structure of refractory MHs with ILM peeling combined with autologous ILM transplantation was largely reduced, and the visual acuity of patients improved significantly.